Legacy of blood : Jews, pogroms, and ritual murder in the lands of the Soviets - Bemporad, Elissa (Oxford University Press, 2019)
"Pogroms and blood libels constitute the two classical and most extreme manifestations of tsarist antisemitism. They were often closely intertwined in history and memory, not least because the accusation of blood libel, the allegation that Jews murder Christian children to use their blood for ritual purposes, frequently triggered anti-Jewish violence. Such events were and are considered central to the Jewish experience in late tsarist Russia, the only country on earth with large scale anti-Jewish violence in the early twentieth century. Boasting its break from the tsarist period, the Soviet regime proudly claimed to have eradicated these forms of antisemitism. But, alas, life was much more complicated. The phenomenon and the memory of pogroms and blood libels in different areas of interwar Soviet Union-including Ukraine, Belorussia, Russia and Central Asia-as well as, after World War II, in the newly annexed territories of Lithuania, Western Ukraine and Western Belorussia are a reminder of continuities in the midst of revolutionary ruptures. The persistence, the permutation, and the responses to anti-Jewish violence and memories of violence suggest that Soviet Jews (and non-Jews alike) cohabited with a legacy of blood that did not vanish. This book traces the "afterlife" of these extreme manifestations of antisemitism in the USSR, and in doing so sheds light on the broader question of the changing position of Jews in Soviet society. One notable rupture in manifestations of antisemitism from tsarist to Soviet times included the virtual disappearance-at least during the interwar period-of the tight link between pogroms and blood allegations, indeed a common feature in the waves of anti-Jewish violence that erupted during the late nineteenth and early twentieth centuries." --